1989
DOI: 10.1177/0148607189013004349
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Anabolic Steroid and Peripherally Administered Intravenous Nutrition in the Early Postoperative Period

Abstract: Sixty patients undergoing colorectal surgery for malignancy were randomized to receive the anabolic steroid stanozolol (n = 30) or to a control group (n = 30). Patients were further randomized to receive on the first 4 postoperative days a) a standard dextrose-saline regimen (DS), b) an amino acid regimen (AA), or c) a glucose-amino acid-fat regimen (GAF) via a peripheral vein. Fat and carbohydrate oxidation rates were calculated pre- and postoperatively using indirect calorimetry. Postoperative nitrogen balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Unlike this study, previous studies in critically ill patients did not measure clinical outcome; however, our study was not specifically powered to show a difference in clinical outcome. Also, our metabolic and nutritional findings are in contrast to some reports 4,5,17 and in agreement with others. 18 A prospective, randomized, double-blind study reported decreased urinary excretion of nitrogen and 3-methylhistidine in men receiving nandrolone 50 mg on day 3 and 25 mg on day 6 after trauma compared with similar patients receiving placebo.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Unlike this study, previous studies in critically ill patients did not measure clinical outcome; however, our study was not specifically powered to show a difference in clinical outcome. Also, our metabolic and nutritional findings are in contrast to some reports 4,5,17 and in agreement with others. 18 A prospective, randomized, double-blind study reported decreased urinary excretion of nitrogen and 3-methylhistidine in men receiving nandrolone 50 mg on day 3 and 25 mg on day 6 after trauma compared with similar patients receiving placebo.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike this study, previous studies in critically ill patients did not measure clinical outcome; however, our study was not specifically powered to show a difference in clinical outcome. Also, our metabolic and nutritional findings are in contrast to some reports 4,5,17 and in agreement with others. 18…”
supporting
confidence: 93%
See 3 more Smart Citations